2020
DOI: 10.1001/jamasurg.2020.1625
|View full text |Cite
|
Sign up to set email alerts
|

Two-Stage Turnbull-Cutait Pull-Through Coloanal Anastomosis for Low Rectal Cancer

Abstract: for the TURNBULL-BCN Study Group IMPORTANCE Two-stage Turnbull-Cutait pull-through hand-sewn coloanal anastomosis seems to provide benefits in terms of postoperative morbidity compared with standard hand-sewn coloanal anastomosis associated with diverting ileostomy and further ileostomy reversal in patients operated on for low rectal cancer. OBJECTIVE To compare 30-day postoperative and 1-year follow-up results of Turnbull-Cutait pull-through hand-sewn coloanal anastomosis and standard hand-sewn coloanal anast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
83
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(89 citation statements)
references
References 60 publications
4
83
1
1
Order By: Relevance
“…Sphincter-preserving surgery (SPS) can be indicated when resection with negative CRM and distal resection margins (DRM) can be achieved, and an adequate anal function can be maintained [ 32 , 33 ]. According to the classification described by Rullier et al [ 28 ], SPS can be adapted to the tumor relation to the sphincter complex to achieve a free distal margin of at least 1 cm; for tumors above the anal sphincter complex, the internal sphincter is preserved, and anal mucosectomy is performed above the dentate line (DL).…”
Section: Surgical Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…Sphincter-preserving surgery (SPS) can be indicated when resection with negative CRM and distal resection margins (DRM) can be achieved, and an adequate anal function can be maintained [ 32 , 33 ]. According to the classification described by Rullier et al [ 28 ], SPS can be adapted to the tumor relation to the sphincter complex to achieve a free distal margin of at least 1 cm; for tumors above the anal sphincter complex, the internal sphincter is preserved, and anal mucosectomy is performed above the dentate line (DL).…”
Section: Surgical Managementmentioning
confidence: 99%
“…For patients with a high risk of AL who refuse to have a protective ileostomy, an alternative CAA can be performed following the Turnbull and Cutait pull-through or delayed CAA [ 32 , 178 ]. In this technique, after rectal resection for SPS, the left colon completely mobilized to be tension-free exteriorized a few centimeters below the anal verge and fixed to perianal skin by 2 stitches and kept in place through the anal canal by the resting pressure of the anal canal ( Fig.…”
Section: Debated Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…This might facilitate better quality of the specimen obtained by TME if combined with an intersphincteric approach from below. A randomized multicentre trial (46 patients in each arm) compared delayed hand-sewn coloanal anastomosis with immediate hand-sewn coloanal anastomosis with diverting ileostomy [22]. The composite 30-day complication rate (including stoma reversal) was 35% (delayed coloanal anastomosis) vs 45% (immediate coloanal anastomosis plus ileostomy), and not statistically significant, leading the authors to conclude that delayed anastomosis is a safe alternative.…”
Section: Ple-line Disruption Published Data Based On the Dutch Colormentioning
confidence: 99%
“…8 The two-stage Turnbull-Cutait (TC) pull-through delayed coloanal anastomosis was suggested as an alternative approach to reduce the incidence of anastomotic complications without constructing a stoma was suggested. 9 A recent randomized trial concluded that the TC procedure is safe and does not increase the postoperative complication rate as compared with standard coloanal anastomosis with diverting ileostomy; however, it omits the need for a covering stoma along with its related complications. 9 The present study aimed to compare the outcome of TaTME with either immediate anastomosis (IA) and covering ileostomy or TC delayed coloanal anastomosis in terms of anastomotic and overall complications, pathologic, oncologic, and functional outcomes.…”
mentioning
confidence: 99%